2019
DOI: 10.1371/journal.pntd.0007566
|View full text |Cite
|
Sign up to set email alerts
|

Unveil the transcriptional landscape at the Cryptococcus-host axis in mice and nonhuman primates

Abstract: Pathogens and hosts require rapid modulation of virulence and defense mechanisms at the infection axis, but monitoring such modulations is challenging. In studying the human fungal pathogen Cryptococcus neoformans , mouse and rabbit infection models are often employed to shed light on the disease mechanisms but that may not be clinically relevant. In this study, we developed an animal infection model using the non-human primate cynomolgus monkey Macaca fascicularis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(65 citation statements)
references
References 53 publications
4
61
0
Order By: Relevance
“…This is most likely due to the greater cost and housing requirements compared to other animal models ( 78 , 79 ). Most studies in non-human primates were conducted decades ago, but a recent 2019 study performed a transcriptome analysis of cynomolgus monkeys ( Macaca fascicularis ) and mice using RNA-Seq during acute C. neoformans infections ( 80 ). The authors found that only about 20 percent of the differentially expressed genes were shared between these two hosts during infection, and they suggested monkeys could be a better model than mice at recapitulating the human response to C. neoformans .…”
Section: Animal Models For Studying Cryptococcosismentioning
confidence: 99%
“…This is most likely due to the greater cost and housing requirements compared to other animal models ( 78 , 79 ). Most studies in non-human primates were conducted decades ago, but a recent 2019 study performed a transcriptome analysis of cynomolgus monkeys ( Macaca fascicularis ) and mice using RNA-Seq during acute C. neoformans infections ( 80 ). The authors found that only about 20 percent of the differentially expressed genes were shared between these two hosts during infection, and they suggested monkeys could be a better model than mice at recapitulating the human response to C. neoformans .…”
Section: Animal Models For Studying Cryptococcosismentioning
confidence: 99%
“…Twelve of the top 30 transcripts induced by the addition of IC (Fig. 1B) have been reported to be associated with cell growth and differentiation, including AREG (42), LIF (38), DC-STAMP (39), INHBA (53), and OCSTAMP (54). The top 30 upregulated transcripts also included three MMPs (MMP1, MMP3, and MMP10) and five cytokine-like molecules (IL-10, LIF, CSF2, IL-36RN, and TSLP).…”
Section: Discussionmentioning
confidence: 99%
“…SnRNA-Seq offers a high resolution characterisation of the neuroimmune response different cell types, subtypes and activation states. A few studies have described successful characterisation of cell-type specific transcriptomic changes that occur in host cells during fungal infections, including C. neoformans ( Li et al., 2019 ; Liu et al., 2014 , 2015 ; Niemiec et al., 2017 ). A recent prolific study used snRNA-Seq to characterise transcriptomic biomarkers in patients who survived, against those who succumbed to cryptococcal immune reconstitution inflammatory syndrome ( Vlasova-St Louis et al., 2021b ).…”
Section: Perspectives For Future Research: Potentially Useful Experimental Models and Techniquesmentioning
confidence: 99%